Gestión de inventario del Market Su Economia en la ciudad de Babahoyo - Bermeo Salazar, Deyalit Karina (2021)
The SU ECONOMIA company is a market in the city of Babahoyo, Ecuador. It is located in the El Salto parish on Malecón and third avenue; the same one that is dedicated to the purchase and sale of staple products, dairy, fruits, vegetables and beverages, providing a plus to your company with the implementation of a neighborhood bank service, activity carried out for several years and has the capacity to serve approximately 200 daily users which have four ATMs for the customer's convenience. The execution of this case study is based on managing how they keep inventory control within the company. The SU ECONOMIA market in the city of Babahoyo is a very repetitive problem in it, because they do not have a detailed record because the entire process of receiving merchandise is done manually and when entering the market they do not have a correct distribution For each product, which means that stocks are not identified, this leads to a serious problem because there are weeks that certain products are lacking and others have accumulated due to not keeping due stock control, since this affects customer service . One of the main problems that the YOUR ECONOMY market has is the inadequate inventory management carried out by workers due to the lack of training, for this reason they do not insist on providing a good service to users causing discomfort on their part and this is This is because there is no good coordination on the administrative side, it is essential to automate the services since they do not have available reports on incoming and outgoing merchandise, an incident factor in shortages.